Advances and Applications of Carbon Capture, Utilization, and Storage in Civil Engineering: A Comprehensive Review - Dhanasingh Sivalinga Vijayan; Selvakumar Gopalaswamy; Arvindan Sivasuriyan; Eugeniusz Koda; Wiktor Sitek; Magdalena Daria Vaverková; Anna Podlasek (Energies)
This paper thoroughly examines the latest developments and diverse applications of Carbon Capture, Utilization, and Storage (CCUS) in civil engineering. It provides a critical analysis of the technology’s potential to mitigate the effects of climate change. Initially, a comprehensive outline of CCUS technologies is presented, emphasising their vital function in carbon dioxide (CO2) emission capture, conversion, and sequestration. Subsequent sections provide an in-depth analysis of carbon capture technologies, utilisation processes, and storage solutions. These serve as the foundation for an architectural framework that facilitates the design and integration of efficient systems. Significant attention is given to the inventive application of CCUS in the building and construction industry. Notable examples of such applications include using carbon (C) in cement and promoting sustainable cement production. Economic analyses and financing mechanisms are reviewed to assess the commercial feasibility and scalability of CCUS projects. In addition, this review examines the technological advances and innovations that have occurred, providing insight into the potential future course of CCUS progress. A comprehensive analysis of the environmental and regulatory environments is conducted to evaluate the feasibility and compliance with the policies of CCUS technology deployment. Case studies from the real world are provided to illustrate effectiveness and practical applications. It concludes by emphasising the importance of continued research, policy support, and innovation in developing CCUS technologies as a fundamental component of sustainable civil engineering practices. A tenacious stride toward carbon neutrality is underscored.